Strategi Usaha Mikro Pengolahan Salak dalam Meningkatkan Perekonomian Desa Wedi Kecamatan Kapas Kabupaten Bojonegoro - Ismi Nur Setyaningtyas; Moh Yusuf Dawud; Noor Djohar (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The research focuses on the growth of snake fruit processing micro-businesses in Wedi Village, Kapas District, Bojonegoro Regency, aiming to develop sustainable strategies for their development. The success of these enterprises hinges on a comprehensive understanding of internal and external factors. The study analyzes the pivotal factors influencing the growth of salak processing micro-enterprises. It prioritizes development strategies, particularly emphasizing the interplay between product quality (an internal factor) and market demand (an external factor). Utilizing the Analytic Network Process (ANP) method via Super Decision Software, the research assesses development factors comprehensively. The pairwise comparison analysis highlights the priority of internal and external factors in influencing the growth of snake fruit processing micro-enterprises. The findings underscore the significant impact of external factors, exceptionally high market demand, which scored 0.52276, indicating its crucial role in driving microenterprise growth. Meanwhile, product quality, though scoring lower at 0.09885, remains a strategic focus for long-term sustainability. The WT strategy, involving strategic raw material procurement and price adjustments, emerged as the most effective alternative strategy with a score of 0.35614. This underscores companies' need to optimize procurement processes and adapt pricing strategies to capitalize on market demand fluctuations. The research contributes valuable insights into the dynamics of salak processing micro-enterprises at the local level. The formulated strategy guides micro-businesses, local governments, and research institutions to foster sectoral growth. By considering both internal and external factors, the strategy aims to impact regional economic development positively and sustainably. In conclusion, the research highlights the critical role of understanding internal and external dynamics in fostering the growth of snake fruit processing micro-enterprises. The strategy prioritizes leveraging market demand while maintaining product quality for sustained growth and economic development in the region.